The Realities of Community Based Natural Resource Management and Biodi versity Conservation in Sub-Saharan Africa - DeGeorges, Paul Andre; Reilly, Brian Kevin (Sustainability, 2009)
This is an historic overview of conservation in Sub-Saharan Africa fro m pre-colonial times through the present. It demonstrates that African s practiced conservation that was ignored by the colonial powers. The colonial market economy combined with the human and livestock populati on explosion of the 21st century are the major factors contributing to the demise of wildlife and critical habitat. Unique insight is provid ed into the economics of a representative safari company, something th at has not been readily available to Community Based Natural Resources Management (CBNRM) practitioners. Modern attempts at sharing benefits from conservation with rural communities will fail due to the low rur al resource to population ratio regardless of the model, combined with the uneven distribution of profits from safari hunting that drives mo st CBNRM programs, unless these ratios are changed. Low household inco mes from CBNRM are unlikely to change attitudes of rural dwellers towa rds Western approaches to conservation. Communities must sustainably m anage their natural areas as "green factories" for the multitude of na tural resources they contain as a means of maximizing employment and t hus household incomes, as well as meeting the often overlooked socio-c ultural ties to wildlife and other natural resources, which may be as important as direct material benefits in assuring conservation of wild life and its habitat. For CBNRM to be successful in the long-term, ful l devolution of ownership over land and natural resources must take pl ace. In addition, as a means of relieving pressure on the rural resour ce base, this will require an urbanization process that creates a midd leclass, as opposed to the current slums that form the majority of Afr ica‘s cities, through industrialization that transforms the unique nat ural resources of the subcontinent (e.g., strategic minerals, petroleu m, wildlife, hardwoods, fisheries, wild medicines, agricultural produc ts, etc.) in Africa.
Keywords: Development; conservation; industrialization; population; wildlife